EKSISTENSI NEGARA DALAM ISLAM (Tinjauan Normatif dan Historis) - Ruslin, Ismah Tita (JPP (Jurnal Politik Profetik), 2015)
This paper describes the existence of state in both concept and political reality in Islam. Discourse on state has been within the study of Islam since classical era. Muslim jurists, normatively position state as dharuriyat (things of importance), while some Muslim thinkers present their ideas on state and the ideal forms and systems of governance, even though there is no such firm and detailed regulations in the Quran and hadith on these issues. Historically, discourse on state may distinguish Islam from other world religions. Islam, since its initial establishment, has been involved with the issue of state and governance, even with political issues at large. Historical facts showed de facto fragmentation within the empire of Islam since 850. The characters of Muslim rulers had nothing to do with the ideal existence of Islamic state. Divisions, conflicts, and even bloodshed had been part of empirical Muslims at that time. It shows that there has been yet no synergy in matching normative Islamic state and historical Islam.